PENGEMBANGAN MEDIA E-COMIC MATEMATIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA MATERI ARITMETIKA SOSIAL UNTUK PESERTA DIDIK KELAS VII SMPN 1 SINTUK TOBOH GADANG - Christina Khaidir; Andi Susanto; Amelia Putri (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This research is motivated by the use of learning media that is not in accordance with the characteristics of students, where currently in the learning process educators only use textbooks and LKPD. Educators lack innovation to develop learning media that are more modern and in accordance with the characteristics of students, such as developing media that uses the internet and digital technology as operating tools. Based on this, research was conducted on the development of mathematical e-comic media based on Contextual Teaching and Learning on social arithmetic material for class VII students who met the valid, practical, and effective criteria. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This study involved 7th-grade students of SMPN 1 Sintuk Toboh Gadang, 6 students were selected as the subject of the one-to-one evaluation and 12 as the small group trial. This research produces a valid, practical, and effective mathematical e-comic based on Contextual Teaching and Learning media. The results of this study indicate that the e-comic media meets the very valid criteria with an average validity of 88.05%, meets the very practical criteria with average practicality of 92.36% for educators and 90.02% for students, meets the effective criteria with acquisition of a complete percentage of 83.33 %.